Stages of team development - Kiriyachenko, Natalia; Bozhok, Natalia (My University, 2014)
Every group of people working together, regardless of the time of existence, structure, activities must pass certain stages of formation and further development of the process.The team is a socially significant group of people with a common purpose and self- government body. Thus, the team’s characteristic features include: a common goal, the collective work, the availability of government.
Keywords: collective work; government; team development; розвиток команди; колективна робота; керівництво; коллективная работа; правительство; развитие команды; кафедра ділової іноземної мови та міжнародної комунікації